Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Discovery Learning Kelas VIII SMP Negeri 6 Sibolga - Metaria Habeahan (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Humans, who are living creatures with intelligence, have the potential to continue to develop. One way of human development is through education. Education for humanity is an absolute need that must be fulfilled throughout life. With education, humans can broaden their insight, be creative, prosperous, happy and be free from being left behind by the increasingly developing times. One of the education children receive is Catholic religious education at school. Studying Catholic Religious Education encourages students to become believers who are able to live and realize their faith in everyday life. In achieving the goals of Catholic religious education, a teacher must have skills in teaching, make careful plans and actively increase knowledge and experience in carrying out his duties. The success of learning depends on the teacher's success in activating students through the teaching and learning process which is supported by educational facilities and infrastructure, appropriate learning models and curriculum. The independent curriculum gives educators the freedom to create quality learning that suits students' needs and learning environment. The independent curriculum emphasizes the Pancasila student profile. In this classroom action research, the researcher focuses on the dimension of having faith in God Almighty and having noble morals and the dimension of critical reasoning. In the process of implementing Catholic religious education, a teacher often encounters problems, for example students are less active in the Catholic religious education learning process, students lack understanding of a concept and low student learning outcomes. There are many factors that cause low student learning outcomes, for example inappropriate learning models, lack of student involvement, the learning process is still teacher-centered and low student interest in reading PAK textbooks. Based on the problems above, teachers can provide meaningful learning experiences by designing the learning process. The learning model that can be applied is Discovery Learning. The use of the Discovery Learning model according to syntax includes providing stimulation, problem statement/identification, data collection, data processing. proof (verification), drawing conclusions/generalization (generalization). The objectives of this research are (1) To find out how to improve student learning outcomes through Discovery Learning for Class VIII SMP Negeri 6 Sibolga. (2) Knowing the increase in achievement targets through the Discovery Learning model in Class VIII of SMP Negeri 6 Sibolga. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research use tests, observation and documentation. The data analysis technique used is comparative descriptive, namely comparing the test scores for action 1 and the test scores after action 2 and then reflecting on them. The research results can be concluded that the Discovery Learning model can improve learning outcomes for class VIII Catholic Religious Education at SMP Negeri 6 Sibolga. This is mainly because through the discovery learning model students learn directly to find new understanding through learning activities designed with various sources. The interaction and communication between teachers and students and communication between students really supports learning activities.